Role of NRP1 in Bladder Cancer Pathogenesis and Progression - Dong, Yang; Ma, Wei-ming; Shi, Zhen-duo; Zhang, Zhi-guo; Zhou, Jia-he; Li, Yang; Zhang, Shao-qi; Pang, Kun; Li, Bi-bo; Zhang, Wen-da; Fan, Tao; Zhu, Guang-yuan; et al. (Frontiers in Oncology, 2021)
Bladder urothelial carcinoma (BC) is a fatal invasive malignancy and the most common malignancy of the urinary system. In the current study, we investigated the function and mechanisms of Neuropilin-1 (NRP1), the co-receptor for vascular endothelial growth factor, in BC pathogenesis and progression. The expression of NRP1 was evaluated using data extracted from GEO and HPA databases and examined in BC cell lines. The effect on proliferation, apoptosis, angiogenesis, migration, and invasion of BC cells were validated after NRP1 knockdown. After identifying differentially expressed genes (DEGs) induced by NRP1 silencing, GO/KEGG and IPA® bioinformatics analyses were performed and specific predicted pathways and targets were confirmed in vitro. Additionally, the co-expressed genes and ceRNA network were predicted using data downloaded from CCLE and TCGA databases, respectively. High expression of NRP1 was observed in BC tissues and cells. NRP1 knockdown promoted apoptosis and suppressed proliferation, angiogenesis, migration, and invasion of BC cells. Additionally, after NRP1 silencing the activity of MAPK signaling and molecular mechanisms of cancer pathways were predicted by KEGG and IPA® pathway analysis and validated using western blot in BC cells. NRP1 knockdown also affected various biological functions, including antiviral response, immune response, cell cycle, proliferation and migration of cells, and neovascularisation. Furthermore, the main upstream molecule of the DEGs induced by NRP1 knockdown may be NUPR1, and NRP1 was also the downstream target of NUPR1 and essential for regulation of FOXP3 expression to activate neovascularisation. DCBLD2 was positively regulated by NRP1, and PPAR signaling was significantly associated with low NRP1 expression. We also found that NRP1 was a predicted target of miR-204, miR-143, miR-145, and miR-195 in BC development. Our data provide evidence for the biological function and molecular aetiology of NRP1 in BC and for the first time demonstrated an association between NRP1 and NUPR1, FOXP3, and DCBLD2. Specifically, downregulation of NRP1 contributes to BC progression, which is associated with activation of MAPK signaling and molecular mechanisms involved in cancer pathways. Therefore, NRP1 may serve as a target for new therapeutic strategies to treat BC and other cancers.